Professional ethics in commercializing blogs as a potential public relations tool - Mohd Helmi Abd Rahim,; Huzooree, Priya Darsanee Mahadavesingh (Penerbit Universiti Kebangsaan Malaysia, 2018)
The research aims to find out whether the responses of bloggers and public relations practitioners have any implication for the practice of public relations, and, whether blogging is an ethical tool to the public relations industry. This research studies the extent of the blogola (paid-post) practice and help understand why organizations still insist on practicing blogola despite the risk of negative public relations. The research also explores the ethical challenge encountered by the public relations industry in the digital age. The researchers evaluate whether new ethical guidelines are needed to resolve the issue of blogola. The researchers adopted the qualitative methodology, namely, the in-depth interview method. The informants are gathered using the convenience sampling, and, fifteen informants were extensively interviewed; being public relations practitioners, bloggers and consumers in Mauritius. The findings suggested that blogs are effective public relations tools to attract customers and boost sales. Deepening into the relationships between bloggers and public relations practitioners concluded that a friendly relationship is good for easy communication and for diversity of blog content. Concerning the ethical dilemma surrounding blogs and public relations, almost all informants agreed that paying bloggers for writing good reviews for the brand is not a violation, provided, the blogger is sincere and transparent about it. As long as the blogger reveals that he or she was compensated in any sort, it is tolerable. The question of new ethical guidelines is a must since social media has completely changed the way public relations work.